(untitled) (Journal of the College of Basic Education, 2022)
Religion has a reproductive power, and the effect of its ideas should be dealt with in areas unrelated to its divine principles. Being shipwrecked and due to the feelings of loneliness, Robison Crusoe’s relationship with God and religion became very strong. Christian belief became the center of life on that deserted island. Therefore, everything that occurs has a connection with Christianity. Consequently, this paper sets itself the task of investigating the religious atmosphere and the main pillar’s that make up the religious background underlying Daniel Defoe’s novel ’Robinson Crusoe’. Accordingly, the present paper opens by highlighting certain points in the political and religious situation during Daniel Defoe’s life. After that, the paper endeavors to discuss what is meant by religion and whether it is a vague or clear concept. Then, the paper expounds the innate linkage between the above mentioned novel and Max Weber’s monograph that uncovers the critical relation between the Protestant religion and the enterprise of Capitalism. Next, the paper moves to illustrate the utilization of certain religious ideas in the novel such as sin and punishment. Then, an attempt is made to explain what Defoe wants to show by portraying Crusoe as a religious teacher teaching Friday about Christianity. Finally, an effort is made to present certain religious Opinions on authority expressed in this novel